Pengembangan dan Validasi Skala Ḥusn al-Ẓann (HZS-7) - Rusdi, Ahmad; Damri, Rafi (Psikis : Jurnal Psikologi Islami, 2024)
Currently, there are not many robust ḥusn al-ẓann instruments available for use with Muslim communities in Indonesia. Although instruments like the 24-item Ḥusn al-ẓann Scale (HZS-24) and the Islamic Positive Thinking Scale (IPTS) exist for measuring ḥusn al-ẓann, they still have psychometric limitations. This study aimed to develop a scale with improved validity, utilizing multiple validation methods, namely the 7-item Ḥusn al-ẓann Scale (HZS-7). A sample of 522 Muslim young adults who were Indonesian citizens participated in the study. The study found that the HZS-7 is a multidimensional instrument, covering two dimensions: ḥusn al-ẓann toward Allah SWT (HZS-A) and others (HZS-O), the factors showed a model fit. The HZS-7 was found to predict on the Rosenberg Self-Esteem Scale (RSES) and the Unconditional Self-Acceptance Questionnaire (USAQ), these results supported nomological validity. Additionally, HZS-7 correlated positively with Positive Thinking (PT) and negatively with Negative Thinking (NT). Almost all the items of HZS-7 showed a weak correlation with social desirability. Overall, The HZS-7 has an acceptable reliability (ω = .713). Future studies could enhance the nomological model, examine convergent validity with more complex outcomes, and further investigate the instrument’s quality